Neutrophil-to-lymphocyte ratio predicts early acute cellular rejection in living donor liver transplantation - Lee, Boram (Ann Surg Treat Res, 2020)
PURPOSE: The aim of this study was to evaluate the predictive value of neutrophil-to-lymphocyte ratio (NLR) in acute cellular rejection (ACR) after living donor liver transplantation (LDLT). METHODS: All consecutive patients who underwent ABO-compatible (ABOc) LDLT from September 2014 to December 2017 were retrospectively reviewed. NLR was calculated on 3 occasions; (1) 4 weeks prior to liver transplantation (LT), (2) the day of LT, and (3) the day before liver biopsy. RESULTS: Among 66 patients who underwent ABOc LDLT, ACR was identified in 15 patients (22.7%) on protocol liver biopsy performed routinely on the postoperative day 7. There was no significant difference in NLR at 4 weeks prior to LT and the day of LT between no-ACR and ACR group (2.98 ± 1.92 vs. 2.54 ± 1.15, P = 0.433; 17.9 ± 8.31 vs. 20.5 ± 13.4, P = 0.393). However, NLR was significantly lower in ACR group compared to non-ACR group just prior to liver biopsy (5.82 ± 3.42 vs. 18.4 ± 17.2, P = 0.035). NLR tends to decrease 3.5 days before the onset of ACR. The area under the receiver operating characteristic curve for optimal cut-off value of NLR was 6.49, with sensitivity and specificity of 80.4% and 73.3% respectively. CONCLUSION: NLR has a potential as a noninvasive predictor of early ACR in ABOc LDLT.